2019
DOI: 10.1107/s2052520619001999
|View full text |Cite
|
Sign up to set email alerts
|

Binding of metal ions and water molecules to nucleic acid bases: the influence of water molecule coordination to a metal ion on water–nucleic acid base hydrogen bonds

Abstract: Edited by P. Macchi, University of Bern, SwitzerlandKeywords: crystal structures; hydrogen bonds; nucleic acid bases; metal ion; coordinated water.Supporting information: this article has supporting information at journals.iucr.org/bBinding of metal ions and water molecules to nucleic acid bases: the influence of water molecule coordination to a metal ion on water-nucleic acid base hydrogen bonds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…17 In accordance with the knowledge that coordination can influence properties of noncovalent interactions, 18,19 in our recent work, we showed that hydrogen bonds involving coordinated water molecules and oxygen or nitrogen atoms of nucleic bases are shorter and stronger compared to similar hydrogen bonds involving noncoordinated water molecules. 20 Similarly, stronger hydrogen bonds involving coordinated hydrogen donors compared to those involving noncoordinated hydrogen donors were observed in other systems. 21,22 This is the consequence of the strong polarization present in coordinated ligands.…”
Section: ■ Introductionmentioning
confidence: 79%
“…17 In accordance with the knowledge that coordination can influence properties of noncovalent interactions, 18,19 in our recent work, we showed that hydrogen bonds involving coordinated water molecules and oxygen or nitrogen atoms of nucleic bases are shorter and stronger compared to similar hydrogen bonds involving noncoordinated water molecules. 20 Similarly, stronger hydrogen bonds involving coordinated hydrogen donors compared to those involving noncoordinated hydrogen donors were observed in other systems. 21,22 This is the consequence of the strong polarization present in coordinated ligands.…”
Section: ■ Introductionmentioning
confidence: 79%
“…Атом кислорода (как более электроотрицательный, чем атомы водорода) оттягивает электронную плотность, образуя частично отрицательный заряд. Благодаря своей структуре молекулы воды могут взаимодействовать друг с другом и с другими биоорганическими молекулами внутри клетки посредством водородных связей (11,12). Все это определяет важность воды как одного из основных элементов клетки в процессе ее функционирования, включая реализацию генетической информации на молекулярном и клеточном уровне.…”
unclassified